Educar pela modelagem matemática no contexto da stem pbl. - FERREIRA, Luan Alves (Universidade Federal do Tocantins, 2023)
It is a research that investigates the possibilities of the STEM PBL projects (Project-Based Learning (PBL) of Science, Technology, Engineering and Mathematics (STEM)) to promote the teaching and learning of mathematics through Mathematical Modeling. Seeks out presents the main elements of the construction of this research based on an educational practice of teaching mathematics, worked dynamically and conceptually. With the objective of carry out this research, observations and analyzes were made on the activity of creating a "bladder driven cart" within the framework of the PARTEM project (Production of Technological Artifacts for Mathematics Education (PARTEM)), of the Licenciatura and Mathematics course, Federal University of Tocantins, Câmpus Cimba. The research approach used was qualitative. The research method was based on a Participant Research – PP. Was used as a data production tool, The interview. The subjects investigated were undergraduate students in Mathematics and Physics. The research space corresponds to the Laboratory of Mathematics - LMAT, where all the processes of the activity were carried out. The theoretical basis was based on the perspective of STEM and Mathematical Modeling. At the end of this work, to the information and data collected, the contributions of this project to the teaching and learning of mathematics were remarkable. By the analysis of the results, it is possible to have a view that the proposal intensified a possibility of promoting the teaching of mathematics by modeling by means of STEM projects.